STUDY REGARDING RELATION BETWEEN LASERFLUORESCENCE VALUES AND DEPTH OF EARLY OCCLUSAL DENTAL CARIES - Claudiu Topoliceanu; Angela Ghiorghe; Galina Pancu; Tiberiu Ţîrcã; Sorin Andrian (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study The aim of study was to determine the relation between laserfluorescence values scale and depth of early occlusal dental caries. Material and methods The in vivo study was performed on a study group of 65 patients and 78 molars with early occlusal dental caries. The selected occlusal surfaces were examined using ICDAS system (clinical exam) and laserfluorescence method (Diagnodent, KAVO) by a single examiner with an experience of two years in the use of ICDAS system and Diagnodent. The depth of demineralisation was recorded with periodontal probe after minimal invasive intervention with bur 330. The categories of early occlusal carious lesions were classified accordingly to Downer indices. Results Enamel occlusal early caries are found in high percentages for ICDAS codes 02 (69%) and Diagnodent values scale 20-24 (76%). Occlusal early caries extended in dentine are found in high percentages for ICDAS codes 03 (80%), 04 (100%) and Diagnodent values scales 25-29 (80%), 35-99 (100%). Conclusions Significant statistical differences were found between different laserfluorescence values range (20-24, 25-29, 30-34, 35-99) related to correlation with demineralization depth.